(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Acha is a potential food security crop that contributes significantly to people’s diet, especially in developing countries such as Nigeria. The suitability of acha-cowpea composite flour and sweet potato starch in the production of extruded snacks was investigated. Acha flour (ACF), cowpea flour (CPF)and sweet potato starch (SPS),were mixed in various proportions of percentage weights (ACF:CPF:SPS)and were used to produce extruded snacks totaling 7 samples: 100:0:0, 90:5:5, 85:5:10, 75:5:20, 70:5:25:, 65:5:30 and50:0:50.The flour blends and starch mixes were analyzed for functional properties while the extruded snacks were evaluated for proximate, physicochemical and sensory properties. There was significant differences (p<0.05) in the functional properties of the flour and starch blends. Oil and water absorption capacity reduced as the proportion of SPS increased while the wettability followed the same trend. Foam capacity and foam stability were higher in all the blends containing cowpea flour. Gelatinization temperature was highest in blends with equal proportions of acha and sweet potato starch.The proximate composition of the extruded snacks were significantly difference (p<0.05) amongst the samples. The result showed that all the samples with cowpea flour had higher protein and ash contents than the control. Samples with 90% AF, 5% SPS and 5% CF performed best in sensory scores particularly in terms of appearance, taste, texture and general acceptability. However, all the samples were generally accepted. It was concluded that nutritious extruded snacks with acceptable sensory qualities can be produced from blends of acha-cowpea flour and sweet potato starch.